Pengaruh Fasilitas dan Kualitas Pelayanan terhadap Kepuasan Masyarakat pada Puskesmas Bandar Dempo Selatan - Martha Tilova; Sastra Mico; Laili Dimyati (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aims to determine the influence of facilities and service quality on public satisfaction at the Bandar Dempo Selatan Community Health Center. A quantitative method with an associative approach was employed. The study sample consisted of 81 respondents selected using the saturated sampling technique. Data collection was conducted through observation, interviews, questionnaires, and literature review. Data analysis involved validity tests, reliability tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²) using SPSS version 26. The results indicate that all research instruments were valid and reliable. The regression equation obtained was Y = 2.657 + 0.224X₁ + 0.359X₂ + e, demonstrating that facilities and service quality have a positive influence on public satisfaction. The t-test results show that facilities have a positive and significant influence on public satisfaction (significance value 0.004 < 0.05), while service quality also has a positive and significant influence (significance value 0.000 < 0.05). The F-test result shows a significance value of 0.000 < 0.05, meaning that facilities and service quality simultaneously have a significant influence on public satisfaction. The Adjusted R-Square value of 0.587 indicates that 58.7% of public satisfaction can be explained by the variables of facilities and service quality, while 41.3% is influenced by factors outside the scope of this study. Service quality is the most dominant variable influencing public satisfaction, with a Beta value of 0.492. Therefore, continuous improvements to facilities and service quality are necessary to enhance public satisfaction at the Bandar Dempo Selatan Community Health Center.